2020
DOI: 10.1039/c9ta11921c
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional CdS@Co9S8/Ni3S2 catalyst for efficient electrocatalytic and photo-assisted electrocatalytic overall water splitting

Abstract: Bifunctional CdS@Co9S8/Ni3S2 for efficient electrocatalytic and photo-assisted electrocatalytic overall water splitting with 86.5% electrical-to-hydrogen (ηETH) and 5.72% solar-to-hydrogen (ηSTH) conversion efficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(25 citation statements)
references
References 106 publications
0
25
0
Order By: Relevance
“…Moreover, the presence of polymer binder could also greatly reduce the speed of electron transfers. No doubt, it is necessary to develop an ideal electrode architecture that not only could decrease the resistance of the substrate with electrode materials but also could facilitate acceleration of the speed of electron transport . Self-supported nanoarrays grown on substrates are favorable for exposure of the whole active site, extenuation of the interface resistance, promotion of mass transport, and acceleration durability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the presence of polymer binder could also greatly reduce the speed of electron transfers. No doubt, it is necessary to develop an ideal electrode architecture that not only could decrease the resistance of the substrate with electrode materials but also could facilitate acceleration of the speed of electron transport . Self-supported nanoarrays grown on substrates are favorable for exposure of the whole active site, extenuation of the interface resistance, promotion of mass transport, and acceleration durability.…”
Section: Introductionmentioning
confidence: 99%
“…Promising light-harvesting materials for solar-tochemical energy conversion include Si, Cu 2 O, and CdS. While CdS can allow photocatalytic OER and HER (or CO2RR) at the same time, 149 Si and Cu 2 O can only allow photocatalytic HER (or CO2RR). 150,151 Unfortunately, these materials are highly unstable in aqueous solution.…”
Section: Mofs As Photosensitizersmentioning
confidence: 99%
“…Heterostructure engineering can adjust electron transfer, active sites and bubble separation due to the synergistic effect of the constructed coupling interfaces so as to boost the activity and durability of the electrocatalysts. [18][19][20][21] It has been reported that combination with conductive materials such as metal, metal alloy and carbon is an effective method to improve the electrocatalytic activity of materials. [22][23][24] Among the various conductive materials, metal alloys are thought to effectively provide additional synergistic properties during electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%